Donor Abilities of Heterocyclic Neutral Lewis Bases in a Nickel(II) Salicylaldehyde 4‐Phenylthiosemicarbazonato Coordination Environment. Issue 4 (10th December 2012) - Cindrić, Marina; Pavlović, Gordana; Hrenar, Tomica; Uzelac, Marina; Ćurić, Manda
Abstract: Eight mononuclear [Ni(sal 4‐Phtsc)· D] thiosemicarbazonato complexes [sal 4‐Phtsc = salicylaldehyde 4‐phenylthiosemicarbazonato ligand; D = imidazole (1 ), methylimidazole (2 ), pyridine (3 ), 4‐aminopyridine (4 ), 4‐methylpyridine (6 ), morpholine (7 ), thiomorpholine (8 ), 2‐aminophenol (9 )] and one dinuclear {[Ni(sal 4‐Phtsc)]2 · D}· 2DMSO [D = 4, 4′‐bipyridine (5 )] complex have been prepared by adding the corresponding Lewis base to the methanol suspension of the parent complex [Ni(sal 4‐Phtsc)(H2 sal 4‐Phtsc)]· CH3 OH. The exchange of the neutral salicylaldehyde 4‐phenylthiosemicarbazone (H2 sal 4‐Phtsc) ligand in the parent complex for the appropriate Lewis base has been confirmed by IR spectroscopy and powder X‐ray diffraction (PXRD) in the solid state. The single‐crystal X‐ray diffraction of seven complexes1 and3 –8 confirmed the formation of the complexes with the Ni II ion, coordinated through O, N, S‐donor atoms from the dibasic salicylaldehyde 4‐phenylthiosemicarbazonato ligand and endocyclic N‐donor atom from the neutral ligand D in the form of a distorted square‐planar coordination. NMR spectroscopy in DMF or DMSO and quantum mechanical calculations have been performed in order to explain and compare the stability of the complexes in solution, depending on the polarity of solvents in the context of donor properties and the nucleophilicity of the heterocyclic Lewis base. The single‐crystal X‐ray data enables a comparison with calculated standard Gibbs energies of binding in the context of crystal packing forces, leading to a general conclusion that the stability of the mononuclear complexes results in the formation of more stable hydrogen‐bonded cyclic dimers as a crystal packing pattern. Abstract : The mononuclear [Ni(sal 4‐Phtsc)· D] thiosemicarbazonato complexes [sal 4‐Phtsc = salicylaldehyde 4‐phenylthiosemicarbazonato ligand; D = imidazole (1 ), methylimidazole (2 ), pyridine (3 ), 4‐aminopyridine (4 ), 4‐methylpyridine (6 ), morpholine (7 ), thiomorpholine (8 ), 2‐aminophenol (9 )] and dinuclear {[(Ni(sal 4‐Phtsc)]2 · D}· 2DMSO [D = 4, 4′‐bipyridine (5 )] complex have been prepared and characterized.